Acute subarachnoid hemorrhage in posterior condylar canal dural arteriovenous fistula: imaging features with endovascular management - Mondel, Prabath Kumar (BMJ Publishing Group, 2014)
A 43-year-old man presented with acute subarachnoid hemorrhage. He was investigated and found to have a rare posterior condylar canal dural arteriovenous fistula (DAVF). DAVFs of the posterior condylar canal are rare. Venous drainage of the DAVF was through a long, tortuous, and aneurysmal bridging vein. We describe the clinical presentation, cross sectional imaging, angiographic features, and endovascular management of this patient. The patient was treated by transarterial embolization of the fistula through the ascending pharyngeal artery. This is the first report of an acutely bled posterior condylar canal DAVF treated by transarterial Onyx embolization with balloon protection in the vertebral artery. The patient recovered without any neurological deficit and had an excellent outcome. On 6 month follow-up angiogram, there was stable occlusion of the dural fistula.